Design of Novel Nanogel Formulation of Naproxen Sodium for Enhanced Anti-inflammatory Effect (Asian Journal of Pharmaceutics (AJP), 2022)
Objective: The main aim and objective of this project study are to developed the nanogel of naproxen sodiumand evaluate them. Naproxen sodium has been used as non-steroidal anti-inflammatory drug (NSAID’s) forits anti-inflammatory and analgesic effect. Topical NSAIDs will penetrate the skin and help reduce painlocally. Oral route causes irritation and ulceration of GIT to avoid this reaction naproxen sodium giventopically. The aim of the present study is to formulate naproxen sodium-loaded nanodispersion and thenincorporated into a gelling agent to produce nanogel which will improve solubility as well as skin permeationof drug. Materials and Methods: Formulations were developed with varying concentrations of polymers likeEudragit RS100 and sodium alginate using modified emulsification-diffusion method. Differential scanningcalorimetric and Fourier transforms infrared (FTIR) analysis was performed to ensure the compatibility ofthe drug and excipients. The gels were tested for clarity, viscosity, spreadability, surface pH, drug contentuniformity, in vitro drug diffusion study, and skin irritation study using rat abdominal skin. Results: FTIRstudies showed no evidence on interactions between drug, polymers, and excipients. The formulations arecharacterized for the particle size and found to be below 150 nm. The drug content in the formulations wasfound satisfactory. The best in vitro drug release profile was achieved with the formulation F4 batch exhibited6 h sustained drug release, that is, 93.05% with desired therapeutic concentration which contains the drug.The formulation showed optimum stability and possessed a sustained drug release during the study period.The nanogel formulation showed the favorable alternative to oral administration for naproxen sodium.Conclusion: From the overall study, it was conclud